Response to 'Reduction in skin cancer diagnosis, and overall cancer referrals, during the COVID‐19 pandemic'. (30th December 2020) - Murray, G.; Roche, D.; Ridge, A.; Hackett, C.; Tobin, A.M.
Abstract : Linked Article: Earnshaw et al. Br J Dermatol 2020; 183 :792–794.